Preparation method and application of a core-shell structure zinc tungstate@zinc hua composite photocatalytic material
By using the core-shell structure of zinc tungstate composite in the photocatalytic materials, the problem of insufficient catalytic activity and cyclic stability in the prior art is solved, and the efficient photocatalytic reduction and cyclic stability of Cr(VI) is achieved, which is suitable for the purification of heavy metal ion wastewater.
Patent Information
- Application Number
- CN202411090959.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-08-09
AI Technical Summary
When existing photocatalytic materials treat Cr(VI)-containing wastewater, their catalytic activity and cycle stability are insufficient, making it difficult to meet the needs of practical applications.
The core-shell structure zinc tungstate@zinhua composite photocatalytic material is used to prepare the material through hydrothermal reaction. The zinc tungstate is coated on the surface of zinc tungstate nanoparticles to form a core-shell structure to improve catalytic activity and cyclic stability.
High-efficiency photocatalytic reduction of Cr(VI) is achieved, with a reduction efficiency of up to 98% under 90 minutes of light, and good photocatalytic cycle stability, which is suitable for the purification of heavy metal ion wastewater.
Smart Images

Figure CN119158565B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of photocatalytic materials for heavy metal ion sewage treatment, and in particular to a preparation method and application of a core-shell structure zinc tungstate@zinc tungstate composite photocatalytic material. Background Art
[0002] Heavy metal ion wastewater is a type of industrial wastewater that seriously pollutes the environment and poses a threat to human health. This type of wastewater mainly comes from industrial production processes such as electroplating, metallurgy, mining, and chemicals. Metal ion wastewater has long-term and persistent hazards. Hexavalent chromium Cr(VI) is a primary carcinogen commonly found in industrial wastewater. It cannot be naturally purified in water or soil, is easily enriched, and endangers human health through the food chain effect. Therefore, purifying Cr(VI)-containing wastewater has important practical significance for the green and sustainable development of the environment and ecosystem.
[0003] At present, photocatalytic reduction method for purifying Cr(VI)-containing wastewater is an efficient, green, energy-saving and environmentally friendly method that has attracted much attention. For example, the Chinese patent document with application number CN201911306279.5 discloses a preparation of an indium oxide-indium sulfide-titanium dioxide composite catalyst and a method for photocatalytic purification of Cr(VI)-containing wastewater. The method first uses indium chloride tetrahydrate, sodium dodecyl sulfate and urea as raw materials to prepare an indium oxide precursor by hydrothermal reaction, and then uses indium oxide, sodium thiosulfate and titanium dioxide as raw materials to prepare an indium oxide-indium sulfide-titanium dioxide composite catalyst by secondary hydrothermal reaction. The indium oxide-indium sulfide-titanium dioxide composite catalyst exhibits good photocatalytic removal activity for Cr(VI). The indium oxide-indium sulfide-titanium dioxide composite is used for photocatalytic reduction treatment of Cr(VI)-containing wastewater, and has the advantages of high removal rate, low treatment cost and environmental friendliness. In addition, the published patent documents show that photocatalysts such as nickel oxide, silver vanadate and nitrogen carbide also have good photocatalytic chromium removal performance.
[0004] Although the photocatalytic materials disclosed in many current patent documents have shown good removal activity in treating Cr(VI)-containing wastewater, in-depth research on the stability of these catalysts in the photocatalytic cycle for treating Cr(VI)-containing wastewater is relatively scarce. Therefore, it is urgent to develop a chromium removal photocatalyst with both high catalytic activity and excellent cycle stability to promote the practical application of photocatalytic technology in the treatment of harmful heavy metal ion wastewater. Summary of the invention
[0005] In view of this, the present invention proposes a preparation method and application of a core-shell structured zinc tungstate@zinc tungstate composite photocatalytic material, the purpose of which is to prepare a photocatalytic material with excellent catalytic activity and cyclic stability in photocatalytic purification of chromium-containing wastewater, and apply it to photocatalytic purification of heavy metal ion wastewater.
[0006] The technical solution of the present invention is achieved in this way:
[0007] A method for preparing a core-shell structure zinc tungstate@zinc tungstate composite photocatalytic material comprises the following steps:
[0008] (1) dissolving sodium alginate and sodium tungstate dihydrate in deionized water to obtain component I; dissolving zinc acetate dihydrate in deionized water to obtain component II; adding component II to component I under stirring to obtain a white suspension;
[0009] (2) The white suspension is transferred to a hydrothermal reactor for hydrothermal reaction to obtain a core-shell structured zinc tungstate@zinc tungstate composite photocatalytic material.
[0010] The preparation principle of the core-shell structure zinc tungstate@zinc tungstate composite photocatalytic material provided by the present invention is: since the solubility product of zinc tungstate is much smaller than the solubility product of zinc alginate, in the reaction system, zinc ions will preferentially react with tungstate ions to generate zinc tungstate nanocrystalline nuclei, and under high-temperature hydrothermal reaction conditions, the zinc tungstate nuclei gradually grow and assemble to form zinc tungstate nanoparticles. As the concentration of tungstate ions in the system decreases, the surplus zinc ions react with alginate ions on the surface of zinc tungstate nanoparticles to generate zinc alginate precursors, and during a long hydrothermal reaction process, the zinc alginate precursors gradually transform into zinc tungstate coated on the surface of the zinc tungstate particles, and finally obtain the core-shell structure zinc tungstate@zinc tungstate composite photocatalytic material.
[0011] The sodium alginate, sodium tungstate dihydrate and zinc acetate dihydrate are all of analytical grade and do not require further purification.
[0012] Furthermore, the molar fraction of zinc flower in the core-shell structure zinc tungstate@zinc flower composite photocatalytic material is 25% to 75%.
[0013] Furthermore, the molar ratio of the sodium alginate to zinc acetate dihydrate is 0.5-2:1; the molar ratio of the sodium tungstate dihydrate to zinc acetate dihydrate is 0.25-1:1.
[0014] Furthermore, the lining of the hydrothermal reactor is made of polytetrafluoroethylene.
[0015] Furthermore, the hydrothermal temperature is 160-200° C., and the hydrothermal reaction time is 24-48 hours.
[0016] The present invention also provides a core-shell structure zinc tungstate@zinc tungstate composite photocatalytic material, which is prepared by the above-mentioned preparation method.
[0017] The present invention also provides the use of the core-shell structure zinc tungstate@zinc sulphate composite photocatalytic material as a catalyst in the photocatalytic reduction reaction of hexavalent chromium.
[0018] Furthermore, the core-shell structure zinc tungstate@zinc China composite material can be used as a catalyst to photocatalytically purify heavy metal ion wastewater, taking the reduction of Cr(VI) heavy metal ions as an example. The photocatalytic activity of the core-shell structure zinc tungstate@zinc China composite material on Cr(VI) was evaluated by a photocatalytic reactor. A 400W metal halide lamp was selected as the light source. 30mg of the core-shell structure zinc tungstate@zinc China composite photocatalyst and 50mL of a 20mg / L potassium dichromate solution were placed in a quartz reaction tube. Stir and disperse for 60min in a dark environment before illumination to allow the core-shell structure zinc tungstate@zinc China composite photocatalyst and the target pollutant Cr(VI) to reach adsorption and desorption equilibrium. During the entire experiment, the circulating cooling water was kept unobstructed so that the reaction was maintained at room temperature and continued. The potassium dichromate solution was sampled at regular intervals, and the change in its absorbance was tested with a spectrophotometer. The change in the concentration of the potassium dichromate solution was analyzed by the change in the absorption value of the optimal absorption wavelength of the potassium dichromate solution.
[0019] The core-shell structure zinc tungstate@zinc flower composite photocatalytic material obtained by the preparation method of the present invention, wherein zinc flower is coated on the surface of zinc tungstate nanoparticles, effectively inhibiting the regrowth and self-agglomeration of zinc tungstate nanoparticles, which is beneficial to expose more catalytic active sites and improve catalytic performance. In addition, the core-shell structure enriches the interface composition of the catalyst, which has a significant effect on accelerating the separation efficiency of carriers. Therefore, the core-shell structure zinc tungstate@zinc flower composite photocatalytic material exhibits excellent photocatalytic purification activity for heavy metal ion wastewater.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The core-shell structure zinc tungstate@zinc flower composite photocatalytic material provided by the present invention realizes the preparation of the core-shell structure zinc tungstate@zinc flower composite photocatalyst through a simple one-step hydrothermal reaction. This strategy is expected to be extended to the preparation of core-shell heterojunction photocatalysts such as zinc molybdate@zinc flower and zinc ferrite@zinc flower.
[0022] (2) The core-shell structure zinc tungstate@zinc flower composite photocatalytic material provided by the present invention can effectively inhibit the regrowth and self-agglomeration of zinc tungstate nanoparticles, and small-sized zinc tungstate nanoparticles can expose more catalytic active sites, thereby improving the catalytic performance. In addition, the core-shell structure of zinc tungstate@zinc flower enriches the interface composition of the catalyst, which can accelerate the separation efficiency of carriers, thereby significantly improving the catalytic performance.
[0023] (3) The core-shell structure zinc tungstate@zinc phosphate composite photocatalytic material provided by the present invention exhibits excellent photocatalytic removal activity for Cr(VI)-containing wastewater, and the reduction efficiency of Cr(VI) after 90 minutes of illumination is as high as 98%. The core-shell structure zinc tungstate@zinc phosphate composite photocatalytic material exhibits good photocatalytic cycle stability, indicating that the core-shell structure zinc tungstate@zinc phosphate composite photocatalytic material provided by the present invention has a good application prospect in purifying heavy metal ion wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 XRD spectra of zinc tungstate@zinc flower, zinc tungstate and zinc flower photocatalytic materials prepared in Example 1, Comparative Example 1 and Comparative Example 2.
[0025] Figure 2 is the SEM picture of the sample. Figure 2 (a) Zinc tungstate; Figure 2 (b) zinc flower; Figure 2 (c) Zinc tungstate@zinc tungstate.
[0026] Figure 3 This is a transient photocurrent density diagram of zinc tungstate@zinc flower, zinc tungstate and zinc flower photocatalytic materials prepared in Example 1, Comparative Example 1 and Comparative Example 2.
[0027] Figure 4 The photocatalytic performance of zinc tungstate@zinc flower, zinc tungstate and zinc flower photocatalytic materials prepared in Example 1, Comparative Example 1 and Comparative Example 2, (a) photocatalytic reduction performance curve of the samples for Cr(VI); (b) kinetic simulation curve of photocatalytic reduction of Cr(VI) by the samples.
[0028] Figure 5 These are the photocatalytic reduction performance curves of zinc tungstate@zinc flower, zinc tungstate@zinc flower-S1 and zinc tungstate@zinc flower-S3 samples prepared in Example 1, Example 2 and Example 3 for Cr(VI).
[0029] Figure 6 The cyclic stability of the photocatalytic reduction of Cr(VI) by the zinc tungstate@zinc tungstate composite material prepared in Example 1.
[0030] Figure 7 This is the XRD spectrum of the zinc tungstate@zinc flower sample prepared in Example 1 before and after the photocatalytic reaction. DETAILED DESCRIPTION
[0031] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0032] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0033] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0034] Example 1
[0035] (1) 1.1890 g of sodium alginate and 2.3093 g of sodium tungstate dihydrate were dissolved and dispersed in 50 mL of deionized water to obtain component I; 2.1950 g of zinc acetate dihydrate was dissolved and dispersed in 25 mL of deionized water to obtain component II, and component II was added dropwise to component I under stirring to obtain a white uniform suspension;
[0036] (2) The suspension was transferred to a closed polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at 180°C for 36 hours, cooled naturally to room temperature, and washed and dried to obtain a zinc tungstate@zinc tungstate composite material.
[0037] Example 2
[0038] (1) 1.9810 g of sodium alginate and 1.6495 g of sodium tungstate dihydrate were dissolved and dispersed in 50 mL of deionized water to obtain component I; 2.1950 g of zinc acetate dihydrate was dissolved and dispersed in 25 mL of deionized water to obtain component II, and component II was added dropwise to component I under stirring to obtain a white uniform suspension;
[0039] (2) The suspension was transferred to a closed polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at 180°C for 36 hours, cooled naturally to room temperature, and washed and dried to obtain zinc tungstate@zinc tungstate composite material-S1.
[0040] Example 3
[0041] (1) 0.3960 g of sodium alginate and 2.9700 g of sodium tungstate dihydrate were dissolved and dispersed in 50 mL of deionized water to obtain component I; 2.1950 g of zinc acetate dihydrate was dissolved and dispersed in 25 mL of deionized water to obtain component II, and component II was added dropwise to component I under stirring to obtain a white uniform suspension;
[0042] (2) The suspension was transferred to a sealed polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at 180°C for 36 hours, cooled naturally to room temperature, and washed and dried to obtain zinc tungstate@zinc tungstate composite material-S3.
[0043] Comparative Example 1
[0044] (1) 3.2990 g of sodium tungstate dihydrate was dissolved and dispersed in 50 mL of deionized water to obtain component I; 2.1950 g of zinc acetate dihydrate was dissolved and dispersed in 25 mL of deionized water to obtain component II, and component II was added dropwise to component I under stirring to obtain a white uniform suspension;
[0045] (2) The suspension was transferred to a sealed polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at 180°C for 36 hours, cooled naturally to room temperature, and washed and dried to obtain a zinc tungstate sample.
[0046] Comparative Example 2
[0047] (1) 3.9620 g of sodium alginate was dissolved and dispersed in 50 mL of deionized water to obtain component I; 2.1950 g of zinc acetate dihydrate was dissolved and dispersed in 25 mL of deionized water to obtain component II, and component II was added dropwise to component I under stirring to obtain a white uniform suspension;
[0048] (2) The suspension was transferred to a sealed polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at 180°C for 36 hours, cooled naturally to room temperature, and washed and dried to obtain a zinc flower sample.
[0049] Material characterization
[0050] Figure 1 The XRD spectra of zinc tungstate@zinc hua, zinc tungstate and zinc hua photocatalytic materials prepared in Example 1, Comparative Example 1 and Comparative Example 2. Analysis shows that the characteristic diffraction peak of the zinc tungstate photocatalytic material prepared in Comparative Example 1 matches the standard card of monoclinic ZnWO4 (JCPDS No.96-210-1675), and the characteristic diffraction peak of the zinc hua photocatalytic material prepared in Comparative Example 2 matches the standard card of monoclinic Zn5(CO3)2(OH)6 (JCPDS No.96-900-7482). The characteristic diffraction peaks of zinc tungstate and zinc hua were detected simultaneously in the zinc tungstate@zinc hua composite material, indicating that the zinc tungstate@zinc hua composite photocatalytic material was successfully prepared by a one-step hydrothermal method.
[0051] Figure 2 The SEM images of zinc tungstate, zinc flower and zinc tungstate@zinc flower photocatalytic materials prepared in Comparative Example 1, Comparative Example 2 and Example 1 are shown in FIG. Figure 2 (a) It can be seen that the zinc tungstate photocatalytic material prepared by the hydrothermal method has a nanorod-like morphology. Figure 2 (b) The zinc hydrate obtained by hydrothermal reaction has a shell-like structure with cortical stacking. Figure 2 (c) is the SEM photo of the zinc tungstate@zinc hua photocatalytic material. It can be clearly seen that there is a layer of flexible wrapping on the surface of the zinc tungstate particles, indicating that the skin-like zinc hua evenly wraps the zinc tungstate nanoparticles to form a core-shell structure zinc tungstate@zinc hua composite material. In addition, the particle size of zinc tungstate@zinc hua is significantly smaller than that of pure zinc tungstate nanorods, indicating that the coating of zinc hua effectively inhibits the self-aggregation and regrowth of zinc tungstate nanoparticles. This is beneficial to increase the specific surface area of the composite material and expose more catalytic active sites, thereby improving its photocatalytic activity.
[0052] Figure 3The transient photocurrent density diagrams of zinc tungstate@zinc flower, zinc tungstate and zinc flower photocatalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2. By comparison, it can be found that the photocurrent density of zinc tungstate@zinc flower composite photocatalyst under illumination conditions is significantly greater than that of zinc tungstate and zinc flower, indicating that the zinc tungstate@zinc flower composite photocatalyst has a faster carrier migration rate and a lower probability of photogenerated electron-hole recombination, which can effectively increase the abundance of photogenerated electrons and corresponding active species in the reaction system, thereby significantly improving the photocatalytic reduction activity of zinc tungstate@zinc flower composite photocatalyst for Cr(VI).
[0053] Performance Testing
[0054] Figure 4 The photocatalytic performance of zinc tungstate@zinc tungstate, zinc tungstate and zinc tungstate photocatalytic materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 for Cr(VI) reduction is given. Figure 4 (a) It can be seen that after 90 minutes of illumination, the photocatalytic reduction efficiency of zinc tungstate, zinc flower and zinc tungstate@zinc flower photocatalytic materials for Cr(VI) was 3.3%, 33.2% and 98.1%, respectively. The photocatalytic reduction efficiency of zinc tungstate@zinc flower composite photocatalyst for Cr(VI) was increased by 94.8% and 64.9% compared with that of simple zinc tungstate and zinc flower, respectively. Figure 4 (b) It can be seen that the photocatalytic reduction rate constant of zinc tungstate@zinc fluoride to Cr(VI) is 1.31×10 - 2 min -1 The photocatalytic reduction rate constants of Cr(VI) are 73.6 and 6.1 times that of pure zinc tungstate and zinc flower, respectively, indicating that the construction of core-shell heterojunction composite structure can significantly improve the photocatalytic purification ability of zinc tungstate@zinc flower composite material for heavy metal ion wastewater. Figure 5 From the intuitive display, we can clearly observe that in the ZnWO4@ZnWO4 composite material, there is an optimal range for the content of ZnWO4. Whether it is excessive or insufficient, it will have an adverse effect on the photocatalytic reduction efficiency of Cr(VI). This shows that precise control of the content of ZnWO4 is crucial to optimizing the photocatalytic performance of the composite material.
[0055] The cyclic stability of a catalyst is one of the important factors in evaluating whether it has the potential for industrial application. Figure 6 The experimental results of the cyclic stability of the core-shell structure zinc tungstate@zinc ore composite material obtained in Example 1 for photocatalytic reduction of Cr(VI) are given. It can be found that the photocatalytic reduction performance of the zinc tungstate@zinc ore composite material for Cr(VI) does not show a significant weakening after 5 cycles. In addition, the zinc tungstate@zinc ore samples before and after the photocatalytic cycle reaction were characterized by XRD (such as Figure 7The results show that the crystal structure of the zinc tungstate@zinc china sample remains relatively stable before and after the photocatalytic reaction. This fully demonstrates that the zinc tungstate@zinc china composite photocatalytic material not only exhibits excellent photocatalytic activity in purifying heavy metal ion wastewater, but also has excellent photocatalytic cycle stability.
[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a core-shell structure zinc tungstate@zinc tungstate composite photocatalytic material, characterized in that: The chemical formula of the zinc flower is Zn5(CO3)2(OH)6, and the preparation method comprises the following steps: (1) Dissolve sodium alginate and sodium tungstate dihydrate in deionized water to obtain component I; dissolve zinc acetate dihydrate in deionized water to obtain component II; add component II to component I under stirring to obtain a white suspension; (2) The white suspension was transferred to a hydrothermal reactor for hydrothermal reaction to obtain a core-shell structured zinc tungstate@zinc tungstate composite photocatalytic material.
2. The method for preparing a core-shell structure zinc tungstate@zinc tungstate composite photocatalytic material according to claim 1, characterized in that: The molar fraction of zinc flower in the core-shell structure zinc tungstate@zinc flower composite photocatalytic material is 25% to 75%.
3. The method for preparing a core-shell structure zinc tungstate@zinc tungstate composite photocatalytic material according to claim 1, characterized in that: The molar ratio of the sodium alginate to zinc acetate dihydrate is 0.5-2:1; the molar ratio of the sodium tungstate dihydrate to zinc acetate dihydrate is 0.25-1:
1.
4. The method for preparing a core-shell structure zinc tungstate@zinc tungstate composite photocatalytic material according to claim 1, characterized in that: The inner lining of the hydrothermal kettle is made of polytetrafluoroethylene.
5. The method for preparing a core-shell structure zinc tungstate@zinc tungstate composite photocatalytic material according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 24-48 h.
6. A core-shell structure zinc tungstate@zinc tungstate composite photocatalytic material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the core-shell structure zinc tungstate@zinc tungstate composite photocatalytic material as claimed in claim 6 as a catalyst in the photocatalytic reduction of hexavalent chromium.
Citation Information
Patent Citations
A method for photocatalytic reduction treatment of hexavalent chromium-containing wastewater using an indium oxide-indium sulfide-titanium dioxide composite.
CN110937653B
Method for preparing tungsten powder
CN104942303A
Preparation method and application of zinc tungstate / zinc benzoate photocatalytic material
CN116273168A